Strategic analysis and knowledge support systems for agriculture and rural development in Africa: Translating evidence into action - Johnson, Michael; Flaherty, Kathleen (International Food Policy Research Institute, 2011)
In this technical guide we describe the Strategic Analysis and Knowledge Support System (SAKSS) concept developed by the International Food Policy Research Institute in response to the capacity gaps typically found in many African countries for generating and translating evidence into action. SAKSS is defined as a collaborative network that acts as a mechanism by which relevant evidence is generated and used to inform agricultural and rural development strategy formulation and implementation. SAKSS brings together two important concepts—“strategic analysis” and “knowledge support systems.” The strategic analysis component describes an integrated framework of analysis that helps identify strategy and investment options for achieving high-end development goals. This analysis is carried out within the context of a knowledge support system, a network that serves the evidence needs of strategy formulation and implementation. By providing a platform for exchange, information, data analysis, and knowledge can be compiled, synthesized, and packaged into evidence that is supplied on a timely and reliable basis to be of use during strategy processes.